Physical properties of heat-treated rattan waste binderless particleboard - Tajuddin, Maisarah; Ahmad, Zuraida; Halim, Zahurin; Maleque, Md Abd; Ismail, Hanafi; Sarifuddin, Norshahida (AIP Publishing, 2017)
The objective of this study is to investigate the effects of heat treatment on the properties of binderless particleboard (BPB) fabricated via hot-pressing process with pressing temperature, pressing time and pressing pressure of 180ᴼC, 5 minutes and 1 MPa, respectively. The fabricated BPB with density in the range of 0.8-0.95g cm-3 was heated in a temperature-controlled laboratory chamber at 80°C, 120°C and 160°C for period of 2 and 8 hours before underwent physical observation, mass loss measurement and thickness swelling test. The samples had remarkable color changes, mainly with samples of treatment temperature of 160˚C, where the color differences were 9.5 and 20.3. This changed the fabricated BPB samples from yellowish brown to dark brown color when treatment conditions increased. Darker color indicates greater mass loss due to severity of chemical component in the powder. Dimensional stability of fabricated BPB was improved with higher treatment temperature as more cellulose cross-linked and hemicellulose degraded that removed the hygroscopicity behavior of powder. These results revealed that heat treatment helped in improving the BPB physical properties, particularly in dimensional stability of boards.